2015
DOI: 10.3354/cr01325
|View full text |Cite
|
Sign up to set email alerts
|

Monthly-to-seasonal predictions of durum wheat yield over the Mediterranean Basin

Abstract: Uncertainty in weather conditions for the forthcoming growing season influences farmers' decisions, based on their experience of the past climate, regarding the reduction of agricultural risk. Early within-season predictions of grain yield can represent a great opportunity for farmers to improve their management decisions and potentially increase yield and reduce potential risk. This study assessed 3 methods of within-season predictions of durum wheat yield at 10 sites across the Mediterranean Basin. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The crossover interaction due to year effects was more pronounced in the other locations; these effects were mainly associated with the total and distribution of rainfall and temperature for rainfed trials. These findings confirm previously reported effects of weather conditions on the GEI in durum wheat in the Mediterranean basin [3,74,75]. Annoceur was characterized by low heritability during both seasons, and it was among the locations where low genetic gain for durum wheat was achieved [76].…”
Section: Dissection Of the Genotype By Environment Interactionsupporting
confidence: 91%
“…The crossover interaction due to year effects was more pronounced in the other locations; these effects were mainly associated with the total and distribution of rainfall and temperature for rainfed trials. These findings confirm previously reported effects of weather conditions on the GEI in durum wheat in the Mediterranean basin [3,74,75]. Annoceur was characterized by low heritability during both seasons, and it was among the locations where low genetic gain for durum wheat was achieved [76].…”
Section: Dissection Of the Genotype By Environment Interactionsupporting
confidence: 91%
“…In the MCYFS, the statistical methods used have inherent flaws, for instance when it comes to unprecedented conditions or yield levels that are out of the usual range of expectations. In recent years an increasing amount of publications have appeared on crop forecasting using a variety of novel methods and approaches ( Becker-Reshef et al, 2010 ; Ceglar et al, 2016 ; Iizumi et al, 2013 ; Ferisse et al, 2015 ; Schauberger et al, 2017 ; Sharif et al, 2017 ) including probabilistic approaches (e.g. Ben-Ari et al, 2016 ), random forest (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The current climate patterns are causing gradual warming of Earth, with the last 5 years (2015–2019) being among the world's warmest while 9 out of 10 warmest years that have been recorded since 2005 (NOAA 2020). The impacts of increased temperature on crop development, yield and quality has been well documented (Porter and Gawith, 1999; Semenov, 2008; Ferrise et al ., 2014; Semenov and Stratonovitch, 2014; Trnka et al ., 2014; Asseng et al ., 2015, 2019). In a study where statistical and process-based models were compared, it has been found that global wheat production will fall by 4–6% per °C of air temperature increase (Liu et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%